An Experimental Performance Evaluation for a Swirl-Vane Separator Using an Air-Water Test Facility - Kihwan Kim (MDPI AG, 2021)
The most important design parameters of a moisture separator to optimize the efficiency of a nuclear power plant are the moisture carry over and pressure drop. An air-water test facility was constructed to evaluate the design parameters for various types of conventional moisture separators in Korea. In this study, a half scale of swirl-vane separator was designed, and test conditions were defined based on the scaling law to cover a wide range of operating conditions. The moisture carry over was measured using an isokinetic sampling system for 34 different flow conditions. The MCO was in range of 0.30–7.05% according to the test conditions. Single and two-phase flow experiments were also carried out to identify the two-phase pressure drop characteristics. Based on the obtained results, the proposed empirical correlation model was extended to a submerged separator and applying these results to a full scale system is discussed in this paper.